Tanispermum, a new genus of hemi‐orthotropous to hemi‐anatropous angiosperm seeds from the Early Cretaceous of eastern North America. Issue 8 (6th August 2018) - Friis, Else Marie; Crane, Peter R.; Pedersen, Kaj Raunsgaard
Abstract : Premise of the Study: Exotestal seeds with characters that indicate relationship to extant Austrobaileyales and Nymphaeales are abundant in Early Cretaceous sediments from Portugal and eastern North America, but their variety and unique features provide evidence of extensive extinct diversity among early angiosperms. Methods: The fossils were extracted from Early Cretaceous sediments from Virginia and Maryland, United States, by sieving in water. After cleaning with HF, HCl and water, they were examined using SEM and SRXTM and compared to seeds of extant and fossil angiosperms. Key Results: A new genus, Tanispermum gen. nov., with four species ( T. hopewellense sp. nov., T. marylandense sp. nov., T. drewriense sp. nov., and T. antiquum sp. nov.) is recognized. Relationship with extant Austrobaileyales and Nymphaeales is indicated by an exotesta of tall palisade sclerenchyma with undulate anticlinal walls forming a jigsaw puzzle‐like surface pattern. However, seeds of Tanispermum differ from those of Austrobaileyales and Nymphaeales in their hemi‐orthotropous–hemi‐anatropous organization. Attempts to place Tanispermum in a phylogenetic context confront a variety of problems, including lack of information on other parts of these extinct plants. Conclusions: The discovery highlights the extent to which the morphology of extant angiosperms is not representative of the diversity that once existed among early‐diverging members of the group. The relictual nature of extant taxa near the base of the angiosperm tree greatly complicates the reconstruction of ancestral character states and emphasizes the need for focused paleobotanical studies to elucidate the extinct diversity that existed early in angiosperm evolution.